SPORT CENTER UNIVERSITAS TANJUNGPURA - Mahaghani, Muhammad Akrabbi; Caesariadi, Tri Wibowo; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Sports are activity carried out with the aim of getting physical and spiritual health. People of Pontianak, especially academic’s civitas at Tanjungpura University, often do sports activities. There are various ways to develop sports activities, one of which is providing a container that can accommodate sports activities, such as the